2009
DOI: 10.1073/pnas.0904867106
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and trait similarity to a native species predict herbivory on non-native oaks

Abstract: Introduced plants tend to experience less herbivory than natives, although herbivore loads vary widely. Herbivores may switch hosts onto an introduced plant for at least two reasons. They may recognize the novel plant as a potential host based on similarity of the plant's traits to the traits of one of its native hosts, a similarity that may or may not exhibit phylogenetic signal. Alternatively, herbivores may feed optimally, assessing which introduced plants provide the best nutrition irrespective of similari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
260
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 218 publications
(289 citation statements)
references
References 43 publications
25
260
4
Order By: Relevance
“…In the current study, we sample 56 oak taxa, representing each of the five major oak clades (Manos et al 1999;Pearse and Hipp 2009), including representatives from eastern North America, western North America, Mexico, Europe, and Asia. Species were selected based on their presence in a 40-year old stand of oaks at University of California, Davis Arboretum.…”
Section: Oak Taxa and Assessment Of Plant Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, we sample 56 oak taxa, representing each of the five major oak clades (Manos et al 1999;Pearse and Hipp 2009), including representatives from eastern North America, western North America, Mexico, Europe, and Asia. Species were selected based on their presence in a 40-year old stand of oaks at University of California, Davis Arboretum.…”
Section: Oak Taxa and Assessment Of Plant Traitsmentioning
confidence: 99%
“…While this sample represents less than 15% of the entire genus, it represents a broad spectrum of the phylogenetic, geographic, and ecological diversity of the genus. Each taxon was represented by three individuals except in cases where fewer were present in the arboretum (Pearse and Hipp 2009). Nomenclature follows the Oaks Names Database (Trehane 2007).…”
Section: Oak Taxa and Assessment Of Plant Traitsmentioning
confidence: 99%
“…The rate at which neophytes are colonised by local herbivorous fauna depends on the degree of phylogenetic similarity of new host plants and their native counterparts, as well as the quality of food, which affects the development of these herbivores (Agrawal and Kotanen 2003;Pearse and Hipp 2009). For example, invasive Prunus serotina Ehrh.…”
Section: Discussionmentioning
confidence: 99%
“…This is biologically similar to environments where the plant may be invading a novel habitat that already contain plants that are phylogenetically similar and thus contain herbivores with trait values that match the invading plant. Many studies have found correlations between phylogenetic distance and antagonistic pressures on plants (Pearse and Hipp 2009;Ness et al 2011;Parker et al 2015). The phylogenetic composition of a community may have as great an effect on the outcome of invading plants as the ecological composition.…”
Section: Discussionmentioning
confidence: 99%